Comparative dimensional tomographic study of the mandibular condyle of individuals with transverse maxillary deficiency - Gonçales, Andréa Guedes Barreto (2017)
Transverse maxillary deficiency is characterized by posterior uni or bilateral crossbite, crowded and rotated teeth, as well as high palate. Its treatment in adult individuals is surgically assisted rapid palatal expansion. The aim of this study was to verify the occurrence of dimensional alterations in the mandibular condyles of patients with TMD submitted to surgically assisted maxillary expansion. Measurements of the mandibular condyles using the DISTANCE tool in cone beam computed tomography iCat software were performed. The values obtained were submitted to statistical analysis by the paired t-test and the results showed statistically significant dimensional reduction in the axial posterior-anterior lateral (-0.74mm), axial posterior-anterior lateral left (-0.90mm) and coronal medium right (-1.24mm) dimensions. The coronal inferior (1.13mm), coronal inferior left (1.78mm) and coronal superior-inferior right (0.76mm) measurements showed statistically significant dimensional increase. The results allowed us to conclude that dimensional alterations occurred in the mandibular condyles in individuals with maxillary transversal deficiency that underwent surgically assisted rapid palatal expansion (SAPE), which can be understood by remodeling, since they are characterized by dimensional increase or reduction, depending on the location where the measurement was performed.